Enhancing sustainability education through experiential learning of sustainability reporting. Issue 6 (24th August 2020) - Sulkowski, Adam J.; Kowalczyk, Wojciech; Ahrendsen, Bruce L.; Kowalski, Robert; Majewski, Edward
Abstract : Purpose: While progress has been made in the realm of teaching about sustainability to business students, integrating sustainability into experiential learning with a systemic mindset has been identified by leading scholars as an area for improvement. The purpose of this paper is to describe a pilot project in which students prepared a sustainability report for a client company and to answer the question of whether the experiment yielded the anticipated benefits. Design/methodology/approach: The paper presents an initiative that was part of an MBA course delivered at the Warsaw University of Life Sciences in Poland by an international team of professors. The multinational group of students was confronted with the task of preparing an integrated sustainability report for a large corporation. Findings: The initiative creates opportunities for both students and commercial organizations to understand large business commercial activities from a sustainability perspective. This paper identifies the next steps for others to build upon. Originality/value: The paper explains the experiential learning opportunity that was created, describes how students rose to meet the challenge, discusses the benefits that accrued to students, professors and a commercial organization and shares some guidance for those seeking to emulate this practice.